Evaluation of Post-Operative Pain Management Techniques in Oral Surgery - Jeswin Singh Mongia; Annaluru Sri Sasank Tejaswee; Vishnu Gowtham Marella; Donka Srilakshmi; Mazen Ahmad Almasri; Pavan Tenglikar; BS Dayanithi (Wolters Kluwer Medknow Publications, 2024)
Objective: This prospective research directed to estimate the efficacy and safety of different post-operative pain management techniques in oral surgery subjects. Methods: Patients scheduled for various oral surgical procedures were recruited from a single oral surgery clinic between January 2022 and December 2023. Inclusion criteria encompassed adult subjects undergoing elective oral surgery under local or general anesthesia. Subjects were randomly assigned to one of three post-operative pain management protocols: Group A received standard analgesics, Group B received combination analgesics, and Group C received non-pharmacological interventions. Pain intensity scores, analgesic consumption, adverse events, and patient satisfaction were assessed at specified intervals post-operatively. Results: Non-pharmacological interventions demonstrated lower pain intensity scores and analgesic consumption compared to standard and combination analgesics. Additionally, the incidence of adverse events was lower in the non-pharmacological intervention group. Statistical analysis revealed significant differences in pain outcomes among the three groups. Conclusion: This prospective research suggests that non-pharmacological interventions may provide effective pain relief with fewer adverse events compared to traditional analgesics in post-operative oral surgery subjects. Implementation of multi-modal pain management approaches tailored to individual patient needs may improve overall pain control and enhance patient outcomes.